Cardiovascular Diabetology - Fisman, Enrique; Tenenbaum, Alexander
Cardiovascular Diabetology considers manuscripts on all aspects of the diabetes/cardiovascular interrelationship and the metabolic syndrome; this includes clinical, genetic, experimental, pharmacological, epidemiological and molecular biology research.